Organizational climate in the small and mediumsized hotel sector in villavicencio - case study: hotels affiliated with cotelco (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
The present work is carried out with the aim of identifying the correlation between job satisfaction and the organizational climate in the SME hotel sector of Villavicencio - case of hotels affiliated with the Colombian Hotel and Tourism Association (COTELCO). The information was collected through surveys, which were carried out on 169 of the 300 employees of the hotel sector studied, using the Likert scale method as a reference, which allows us to measure certain variables that influence the development of their economic activity and therefore the productivity of the company. Thus, determining the degree of general satisfaction that the employees may have regarding several factors that directly affect their performance and their way of acting in their daily activities. In relation to the descriptive quantitative use of each variable and a correlation analysis, using the Pearson coefficient, the results have shown the existence of a positive correlation between the variables dealt with, a finding that reinforces the existing hypothesis in this regard.
Keywords: job satisfaction; pymes; organizational climate; productivity; correlation